Evolution of Malaysia’s technology transfer model facilitated by national policies - Rahman Hamdan, Abdul; Syazli Fathi, Mohamad; Mohamed, Zainai (International Journal of Engineering and Technology, 2018)
The government of Malaysia has introduced several national policies to facilitate industrialisation and technology development in the country throughout the years. However, the effectiveness of this policy in facilitating technology transfer has never be measured quantitatively. The objective of this paper is to review the evolution of Malaysia's technology transfer model and process since Malaysia gained its independence. This paper will look into the past and current national policies that have facilitated the technology transfer process in the country. A literature review was conducted on various frequently used technology transfer model since 1940s and compare it to the technology transfer process evolution in the country. From the analysis, the national policies introduced over the years have a direct and indirect effect on the technology transfer process in the country. However, the effectiveness of technology transfer model that was facilitated by the policy was never measured quantitatively. Further study needs to be conducted in measuring the efficiency of the technology transfer process that facilitated by a specific policy introduced by the government. The factors and sub-factors affecting the technology transfer process facilitated by this specific policy also need to be identified so that further improvement can be proposed.Â Â